دراسة متانة وصلات اللصق وتحسنيها - رامي منصور; لطيفة الحموي; رانيا حسن (Tishreen University, 2017)
يهدف البحث إلى دراسة متانة وصلات اللصق التراكبية البسيطة، لصفائح الألمنيوم المطبقة كثيرا في التطبيقات الهندسية، وتم التحقق من تأثير كل من مسافة التداخل، وقيم الخشونة السطحية للسطوح الملصقة على متانة القص للوصلات المنجزة، حُضّرت الوصلات الملصقة باستخدام نوعين من المواد اللاصقة، وهما الايبوكسي والأكريليك ونُفذت الاختبارات التجريبية تحت تأثير حمل الشد حتى الكسر باستخدام آلة الشد. أظهرت النتائج إمكانية زيادة متانة الوصلات الملصقة بزيادة طول التداخل، وزيادة قيم الخشونة السطحية للسطوح الملصقة وحدد لاصق الأكريليك بأنه اللاصق الأمثل في الاختبارات المنفذة، وذلك تبعا لنمط الفشل الحاصل في العينات المختبرة، والتي لم تتعرض فيها منطقة اللصق للانهيار مع زيادة الحمولة المطبقة. The aim of this study is to determine strength of adhesive single-lap joints of Aluminum alloys which are widely used in geometric applications. It was investigated to define the influence of overlap length and surface roughness value on shear strength of achieved adhesive joints. It was used Epoxy and Acrylic adhesives to prepare adhesive joints and all the specimens were subjected to axial tensile tests and the results are presented as a comparison. Results of those tests showed that shear strength increased with increasing each of overlap length and surface roughness of adherends and Acrelicadhesiveproduced better results according to failure mode of tested samples.